Analisis Optimasi Penjadwalan dengan Metode Precedence Diagram Method pada Proyek Konstruksi Pembangunan Rumah Sakit Regina Maris Medan - Muhammad Rizky; Ahmad Perwira Mulia Tarigan; Gina Cynthia R Hasibuan (Syntax Corporation Indonesia, 2024)
Good project management in the process of implementing private residential buildings, private buildings, and infrastructure buildings intended for the public interest, is one of the factors for the progress of a country. The study focused on the construction of the Regina Maris hospital in Medan, which is one of the developments in the complex category. The purpose of this study is to provide the results of an analysis of the development in order to achieve goals or targets that can provide efficient use of time, cost and quality which are considered to be the main supporting factors in a development.The research was carried out with three main activity stages, namely the identification stage, the data compilation stage and problem analysis and the use of the Precedence Diagram Method (PDM) method to analyze the optimization of work implementation schedules. The identification stage was carried out in the study area, beginning with observing the condition of the construction implementation, and deepening the identification of environmental conditions or internal/external factors that could hinder work. The results of the identification stage, accompanied by identification of problems and factors that can hinder work, are then used as initial data from the preparation stage of optimizing work implementation schedules using the Precedence Diagram Method